The accidental beauty queen - Wilson, Teri (Gallery Books, 2018)
Sometimes being pushed out of your comfort zone leads you to the ultimate prize. Charlotte and Ginny Gorman might look alike but they're completely different in every other way. Bookish Charlotte loves her job as an elementary school librarian, while her twin sister is an Instagram-famous beauty pageant contestant. Ginny has been chasing a crown since she was old enough to enunciate the words world peace, and she's not giving up until she's crowned Miss American Treasure. Dragging Charlotte to the pageant with her for good luck, Ginny's winning plan goes awry when she has a severe allergic reaction to dinner the night before the competition. A trip to urgent care confirms that she won't be back in beauty queen form for at least three days. After a few tears and a whole lot of begging, Charlotte agrees to take her sister's place in the pageant. Overnight, she's thrown into the glittery world of hair extensions, false eyelashes, and push-up bras. Charlotte realizes that there might be more to the pageant circuit than just a sparkly crown.